Perceptions and Experiences With Healthcare Providers Among People Navigating Reproductive and Fertility Decisions - Marta Bornstein; Anna C. Church; Kaleb Masterson; Alison H. Norris (SAGE Publishing, 2024)
Objectives: Primary healthcare providers have an important role in helping people manage their reproductive health and fertility by assessing pregnancy intentions to inform the provision of contraception and/or preconception care. This study explores how women navigating fertility decisions perceived and experienced interactions with their healthcare providers around their fertility. Methods: We conducted in-depth interviews (N = 17) and focus groups (N = 17 groups) with 65 women aged 18 to 35 years about fertility, infertility, and reproductive planning. Two researchers coded 2 transcripts using thematic and inductive methods and met to develop a structured codebook. We then applied the codebook to the remaining transcripts. Results: In all interviews and focus groups, participants discussed their interactions with healthcare providers around fertility. Three central themes emerged in the data, including a desire for more information from healthcare providers about fertility; experiences of having fertility concerns dismissed by healthcare providers (eg, ability to become pregnant when desired); and, feelings that healthcare providers lacked sensitivity in discussing fertility related issues. Notably, these themes were present, even among participants who were not trying to become pregnant or who did not wish to become pregnant. Conclusion: Participants wanted information about fertility from their primary healthcare providers that they felt was lacking. Moreover, participants wanted their healthcare providers to engage with them as multifaceted individuals with current needs as well as future plans regarding fertility. While healthcare providers regularly assess pregnancy intentions, they may need to make a concerted effort to address fertility concerns among both those who want to pursue pregnancy and those who do not wish to become pregnant immediately.